Experiências leitoras de estudantes da Universidade Federal de Sergipe - Lima, Ana Paula Ferreira de (2020)
This course conclusion work aims to map and analyze Reading experiences from students of the Campus Professor Alberto Carvalho from Universidade Federal de Sergipe, with focus on the reader’s educational process. This research encompasses the formation of readers. The specific objectives point to: a) Identifying traces that surround reading practices; b) Pinpoint experiences of contact with reading; and c) Conceptualize these reading formation processes. It is intended to be a qualitative field research concerning nature and data analysis. The means of this study were survey and pictures of the readers. The readers-subjects included students from several courses such as Business Administration, Accounting Sciences, as well as Bachelor of Arts in Portuguese, Chemistry and Pedagogy. The collected data were worked in the light of theorists Roger Chartier (1998), Márcia Abreu (2006) and Pierre Nora (1993), articulated with other works regarding “reading practices and memories”. The results of this work reveal the distinctiveness of the readers which appropriate the act of reading in line with their experiences.